Health Promotion to Women of Fertile Age (WUS) About the Selection of Family Planning Contraceptives in the North Margahayu Sub-district, Bandung City - Tri Ardayani; Fahmi Fuadah; Gurdani Yogisuntanti; Linda Hotmaida; Neti Sitorus (Asosiasi Profesi Multimedia Indonesia, 2023)
Women of childbearing age experience many obstacles in choosing contraception. One of them is due to a lack of knowledge about the safety of the method used and the husband is not allowed to solve the problem so that he does not experience pregnancy. The purpose of doing this community service is to provide information to WUS about the family planning program so that WUS have knowledge and understanding of family planning devices so that they can properly spacing pregnancies and manage the number of children they have. The target of this community service activity is women of childbearing age (WUS), totaling 35 people, carried out offline on Wednesday, August 17 2022, 09.00 to 10.00 WIB, at the RW office. This community service activity is carried out with the help of LCD media and power point, the time for giving the material is 30 minutes. To evaluate health promotion activities by providing post-test questions about the material that has been provided by the resource person. The results obtained after being given health promotion were an increase in knowledge of WUS by conducting evaluations by asking questions about the material that had been conveyed by the informants, all participants were able to answer well. Health promotion is expected not only to increase WUS knowledge but also to change behavior so that the knowledge gained can be applied in everyday life.